Determining the risk of miscarriage in genetic forms of thrombophilia - Loskutova, Tetiana; Petulko, Albina (ScienceRise: Medical Science, 2023)
The aim: to study the distribution and influence of coagulation factor gene polymorphisms and endothelial dysfunction on the development of recurrent pregnancy loss. Materials and methods: a prospective case-control study included 109 pregnant women in the 1st trimester with habitual miscarriage and 34 conditionally healthy pregnant women with an uncomplicated obstetrical anamnesis without risk factors for miscarriage. Genetic polymorphisms of coagulation and fibrinolysis factors (1691 G→A FVL, 20210 G→A prothrombin, 675 5G/4G PAI-1, 455 G→A fibrinogen β), as well as endothelial dysfunctions (192 Q→R PON-1, 677 C → T MTHFR) were investigated using allele-specific polymerase chain reaction. Results: Pathological polymorphisms of the genes of the hemostasis system and endothelial dysfunction play a significant role in the development of miscarriage, namely such pathological genotypes as 1691 GA of factor V Leiden - increases the risk by 5.3 times (95 % CI 1.5-18.5), 20210 GA of prothrombin - by 26.47 times (1.6-445.7), 675 4G/4G PAI-1 - by 7, 5 times (1.7-33.79), -455AA fibrinogen β - 9.7 times (1.3-74.16), 677 CT MTHFR - 2.6 times (1.0-6.2), 677 TT MTHFR - 21.7 times (1.3-368.6). Multigenic forms of thrombophilia predominate in the majority of patients with miscarriage and account for 76.1 % (p<0.001, OR=12.31, 95 % CI 4.8-31.55). It was determined that the simultaneous presence of two pathological polymorphisms increases the risk of miscarriage by 3.88 times (OR 3.38; 95 % CI 1.26-9.97), and three ones - more than 2.5 times (OR 2.66; 95 % CI 1.02-7.19). Conclusions: the course of pregnancy against the background of pathological polymorphisms of the genes of the hemostasis system and endothelial dysfunction significantly increases the risk of habitual miscarriage, which should be considered when planning a pregnancy in women with habitual miscarriage